Empirical Study on the Relationship between Market Share, Advertising Density and Ratio of Sales - Yucheng, He; Wenna, Ding; Qian, Zhang; Guang, Yang; Fangqiang, Li (Journal of Food Technology Research, 2015)
The causal relationship between market share, advertising density and ratio of sales has been widely discussed in academic circles. This paper examined the extent of reaction and the reverse causal relationship between advertising, concentration, and performance. Secondary data on the enterprises’ operating income, total profits and advertising costs of the mid-range and high-end liquor enterprises, covering the period 2003-2011, were sourced from the financial statements. The simultaneous-equations model was employed to examine the mutual relationship of advertising, concentration and performance. The results of the simultaneous-equations model show that increased advertising density did not contribute to acquiring a higher market share for the mid-range and high-end liquor enterprises. We also found that a higher ratio of sales stimulated the enterprises to invest more in advertising costs; however, it did not promote the increase of market share.